IDENTIFIKASI Salmonella sp. Dan Staphylococcus aureus Serta HITUNG JUMLAH TOTAL BAKTERI PADA MARGARIN - Fines Dwi Martanda (Jurnal SainHealth, 2019)
Margarine is a product of emulsion, both semisolid and liquid made from vegetable fats. The composition of margarine includes fats, water, vitamins A and vitamin E as well as other ingredients. At SNI 7388:2009 on the maximum limit of microbial contamination there are some bacteria that are often found in foodstuffs margarine including Salmonella sp. and Staphylococcus aureus. Salmonellasp. bacteria can lead to deman enteric, diarrhea, nausea, stomach cramps. Staphylococcus aureusbacteria are the most frequently used agents to cause skin sepsis, enteric infections, septic and pneumonia. The purpose of research is to know the contamination of Salmonella sp. and Staphylococcus aureus as well as ALT bacteria in margarine. The method used is laboratory experiments. From the results of the identification of 10 samples of Salmonella sp. and Staphylococcus aureus bacteria. As well as the result ALT bacteria meet the quality requirements of margarine.